Benjamin Tappan Jr. (1773-1857) as a Naturalist and Malacologist - Ralph W. Dexter (Hello World!, 1971)
Benjamin Tappan, Jr. was born 25 May 1773 at Northampton, Massachusetts, the eldest of seven sons. After a common public school education, he worked with his father, a merchant at Northampton, as a goldsmith and silversmith until he was apprenticed to learn copperplate engraving and printing. His hobbies were portrait painting, which he studied under the famous Gilbert Stuart, and natural history. Following his student days at Yale, he studied law for three years and was admitted to the Bar at Hartford, Connecticut, in 1799.